KONEKSI INTERNET DENGAN MODEM HANDPHONE PADA SISTEM OPERASI LINUX UBUNTU 9.04 (Studi Kasus Pada Aga Prima Computer) - Akhmad Majid (Universitas Sains dan Teknologi Komputer, 2022)
The development of science and information technology is very rapid in today's world. As part of the world community, we certainly don't want to be left behind in developing technology and information. There are many ways that can be taken to find out about technological developments. One of them is the internet. In this case, the internet connection certainly cannot run without a modem. Likewise with AGA PRIMA COMPUTER which is engaged in computer service and assembly services. Today many people need the internet both at work and at home. However, there are still many people who complain about internet security weaknesses with the Windows operating system. Thus the author tries to develop an easy and safe way to surf the Internet, namely using an HP modem (here the author uses an HP nokia 6120C modem) on the Ubuntu 9.04 linux operating system which is expected to reduce problems in surfing. By providing additional applications for linux in the form of firestarter as a firewall and avast which is used as an antivirus. And in checking the stability of the internet connection using the site www.bwmeter.i2.co.id.